Effects of semi-permeable membrane covering coupled with intermittent aeration on gas emissions during aerobic composting from the solid fraction of dairy manure at industrial scale. (15th July 2021) - Fang, Chen; Yin, Hongjie; Han, Lujia; Ma, Shuangshuang; He, Xueqin; Huang, Guangqun
Graphical abstract: Highlights: Membrane coverage technology (CT) was suitable for dairy manure aerobic composting. CH4 and N2 O emission decreased by 99.89% and 60.48% in the CT group. The total greenhouse gas emission decreased by 70.76% in the CT group. Intermittent aeration promoted the greenhouse gas emission reduction performance. Aeration period repaired the water layer to reduce NH3 emission. Abstract: In this study, the effects of covering the compost pile with a semi-permeable membrane in combination with intermittent aeration on the gas emissions during aerobic composting from the solid fraction of dairy manure at industrial scale were investigated. A large-scale composting experiment was carried out to compare a membrane-covered (CT) group with a control (CK) group. The results indicated that the CT group could maintain a suitable aerobic and positive micro-pressure environment. The carbon dioxide, methane, nitrous oxide, and ammonia emissions outside the membrane during the aeration interval were reduced by 64.23%, 70.07%, 54.87%, and 11.32%, respectively, compared with that inside the membrane. It was also determined that the methane and nitrous oxide emissions from the CT group were reduced by 99.89% and 60.48% relative to the CK group, confirming that the combined process represented a novel strategy for reducing gas emissions during dairy manure composting.